Dietary Copper Plays an Important Role in Maintaining Intestinal Barrier Integrity During Alcohol-Induced Liver Disease Through Regulation of the Intestinal HIF-1α Signaling Pathway and Oxidative Stress - Lin, Hongwei; Chen, Dazhi; Du, Qianjing; Pan, Tongtong; Tu, Hanxiao; Xu, Yuedong; Teng, Teng; Tu, Jingjing; Li, Ji; Lin, Zhuo; Wang, Xiaodong; Xu, Lanman; et al. (Frontiers in Physiology, 2020)
Impaired intestinal barrier function and oxidative stress injury play critical roles in the pathogenesis of alcoholic liver disease (ALD) and recent investigations reveal a role of dietary copper in the liver and intestinal barrier function. Therefore, the current study is to investigate the mechanisms and role of dietary copper on alcohol induced liver diseases. C57BL/6 mice were used to create alcoholic liver disease model with Lieber-DeCarli diet containing 5% alcohol and fed with different concentrations of dietary diets adequate copper (6 ppm, CuA), marginal copper (1.5 ppm, CuM) or supplemental copper (20 ppm, CuS). Caco-2 cells were also employed to expose to ethanol and different concentrations of copper. Damages of the liver and intestine were evaluated by transaminases and histology staining, as well as cell proliferation, oxidative stress and mitochondrial memebrane potential. The results indicate alcohol diet causes liver injury and disruption of intestinal barrier function as well as decreases genes expression such as HIF-1α, SOD1, and GPX1. However, supplemental dietary copper can revert these changes, but marginal dietary copper can worsen these changes. In animal experiments, marginal dietary copper or low level of dietary copper showed detrimental effects on intestinal barrier function and genes expression. In conclusion, supplemental dietary copper has benefial effects on the liver and intestinal barrier function as well as gene expression. However, marginal dietary copper shows detremental effects on these paremeters.